AN OVERVIEW OF STRATEGY IN LANGUAGE LEARNING - Wahyuni, Sri (STKIP Bina Bangsa Getsempena Banda Aceh, 2015)
This article describes about Strategy in Language Learning. Learning strategy are steps taken by students to enhance their own learning. Strategies are especially important for language learning because they are tools for active, self-directed involvement, which is essential for developing communicative competence. Appropriate language learning strategies result in improved proficiency and greater self-confidence. Owing to conditioning by the culture and the educational system, however, many language students (even adults) are passive and accustomed to being spoon-fed. They like to be told what to do, and they do only what is clearly essential to get a good grade-even if they fail to develop useful skills in the process. A general overview of the system in language learning strategies are divided into two major classes: direct and indirect. These two classes are subdivided into a total of six groups (memory, cognitive, and composation under the direct class; metacognitive, affective and social under the indirect class). Direct strategies and indirect strategies support each other and each strategy is capable in connecting with and assisting for every other strategy.Â Â Key Words: Â Strategies, Language Learning